Digestibility and Nitrogen Balance of Male Bligon and Kejobong Goat Fed Peanuts Straw - Yusiati, Lies Mira; Hanim, Chusnul; Putra, Dianestu (2016)
Bligon and Kejobong are Indonesian local goat breeds which are highly potential to be developed due to their good performances. The problem commonly arise in goat fattening is feed supply which is less than the requirement as it is depends on season. Therefore, the study on alternative feed stuffs that can fulfill the needs of the animal, for instance nutrient contents and its quality as well as its availability in area of goat reared is needed. One of the potential feedstuff for goat was agriculture by products such as peanut straw which is easy to find during harvesting time. Usually farmers use agriculture by products such as peanut straw as sole diet for ruminant. The question is that the diet can fulfill N requirement of the ruminants. Ruminant require protein in the diet to supply N for rumen microbes activity and for animal tissue metabolism. Microbial requirement are met at 6-8% crude protein in the diet while animal requirement range from 7-20% in the diet depending upon species, sex, and physiological status ( Huston, and Pinchak, 2016) Measurement of Nitrogen (N) balance is a useful and accurate method to evaluate the nutrient quality of feedstuff, especially the values of nitrogen to ruminants. The method were used to evaluate the multipurpose trees which may suitable for feed supplements (Jetana et al. 2010), to evaluate the effect of physical treatments of feedstuff on N utilization (Mbewe, et al. 2014). The method also used to evaluate the response of different species (Yusiati et al., 2000) and different breed (Elamin, et al., 2012, Yusiati et al., 2015) of ruminants to feedstuff or diets offered in order to increase efficiency of livestock production. Based on the review, it is necessary to evaluate a single feed from peanuts straw to supply protein requirement of goats, either Bligon or Kejobong, using nitrogen balance experiment.